39th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2003
DOI: 10.2514/6.2003-4506
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Analytical Methods for Solid Rocket Motor Grain Analysis

Abstract: Analytical methods for solid rocket motor grain design are proving to be tremendously beneficial to some recent efforts to optimize solid-rocket propelled missiles. The analytical approach has fallen out of favor in recent decades; however, for some classes of grains, the analytical methods are much more efficient than grid-based techniques. This paper provides a review of analytical methods for calculating burn area and port area for a variety of cylindrically perforated solid rocket motor grains. The equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…It is observed that propellant can be manufactured by both casting and extrusion methods. Since geometric details of grain design are missing in most of the recent texts, analytical methods for determining burn surface area and port area as a function of burn distance for a variety of cylindrically-perforated solid rocket motor grains has been reviewed 16 . Star, long-spoke wagon wheel, dendrite grains are considered, but the simple grain design is not visited in open literature exclusively.…”
Section: Configuration Detailsmentioning
confidence: 99%
“…It is observed that propellant can be manufactured by both casting and extrusion methods. Since geometric details of grain design are missing in most of the recent texts, analytical methods for determining burn surface area and port area as a function of burn distance for a variety of cylindrically-perforated solid rocket motor grains has been reviewed 16 . Star, long-spoke wagon wheel, dendrite grains are considered, but the simple grain design is not visited in open literature exclusively.…”
Section: Configuration Detailsmentioning
confidence: 99%
“…The coefficients of determination were high for response surfaces, and indicated that the fitted quadratic models accounted for more than 92% of the variance in the experimental data. Base on p values, the regression coefficient that was significant at p < 95% were selected for the models that resulted in Equations (9) to (13). Analyses of variance (ANOVA) were conducted to evaluate the adequacy and consistency of the models using F-statistic.…”
Section: Performance Equation For Composite Formulationmentioning
confidence: 99%
“…Therefore optimizing the composite formulation to enhance good performance becomes an essential issue. The need to apply process optimization as an essential tool demonstrated high efficiency in selecting optimal process variables in many chemical processes [13]. Among process optimization tools that have been effectively applied to chemical processes is response surface methodology (RSM) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the design and development of solid propellant rocket motors, an accurate and reliable internal ballistics model provides a physical understanding of the main internal ballistic driving phenomena, besides being used for design optimisation through parametric analysis of the available design options [1][2][3][4] . A good internal ballistics model is also required for the characterisation of the solid rocket motor performance and mission capabilities for both nominal and non-nominal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…are generally carried out using analytical methods 1,5 . The grain geometry evolution of a complex initial geometry grains like conocyl or finocyl require use of generalised three-dimensional computer programs using different algorithms and grain burnback evaluation methodology 5 .…”
Section: Introductionmentioning
confidence: 99%